Key factors associated with self-care among patients with heart failure: A scoping review of cross-sectional studies - Vatmasari, Ratih A.; Putra, Kuswantoro R.; Windarwati, Heni D.; Hany, Alfrina (Narra X, 2025)
Heart failure is a life-threatening condition with increasing prevalence and mortality rate worldwide, often resulting in frequent hospitalizations and reduced quality of life. Effective self-care behaviors are essential for minimizing adverse health effects among patients with heart failure. The aim of this study was to identify and synthesize factors influencing self-care among individuals with heart failure. Articles published in English between 2017 and 2022 were retrieved from Google Scholar, PubMed, and ScienceDirect using predefined Boolean search terms, including 'self-care', 'factors', 'influence', 'heart failure patients', and 'cross-sectional study'. Of 740 records screened, 21 studies met the inclusion criteria. The identified factors were thematically categorized into sociodemographic, psychological, cognitive, and social domains. Sociodemographic factors (age, education, marital status, and New York Heart Association (NYHA) class), health literacy, self-efficacy, depression, and family support were consistently identified as critical determinants. Self-efficacy emerged as a central factor, influencing the relationship between depression and knowledge of self-care performance. Family support proved to be a significant facilitator of effective self-care. These findings suggest that multiple interrelated factors contribute to suboptimal self-care among patients with heart failure. Addressing these determinants may inform the development of effective, culturally sensitive self-care interventions and guide nursing practice and health policy aimed at improving heart failure management.